Quality Assessment of Images with Multiple Distortions using Combined Metrics - Okarma, K. (Elektronika ir Elektrotechnika, 2014)
In this paper the problem of quality assessment of images containing various types of distortions is concerned. Many image quality metrics proposed during last decade are quite well correlated with human perception of various kinds of distortions with the assumption that only a single type of distortions is present in the image. One of the main reasons of such approach is the lack of datasets containing subjective quality assessment results of multiply distorted images. However, after the development of LIVE Multiply Distorted Image Quality Database, a new challenge related to verification of usability of known metrics as well as the development of new ones has appeared. In this paper, the results of such verification is presented not only for some well-known metrics but also for recently proposed combined metrics together with the proposed new combined metrics optimized for multiply distorted images. The new metrics outperform previously proposed ones in the aspect of linear correlation with subjective evaluations of images containing multiple distortions. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.7284